The divine existence: Ontological discourse of al-ghazali (d. 1111) and maimonides (d. 1204) - Senin, Nurhanisah; Amat Misra, Mustafa Kamal; Mohd Akib, Mohd Manawi; Mohd Khambali @ Hambali, Khadijah; Wan Ramli, Wan Adli (Gyandhara International Academic Publications, 2019)
Purpose: This paper aims to elucidate al-Ghazali and Maimonides ontological arguments in proving God’s existence by analysing their theological writings. In the golden age of Islamic civilization, fellow Jewish and Christian were seen to be engaged in theological discourse with Muslim scholars. In adjacent, al-Ghazali and Maimonides were seen playing vital roles in affirming the existence of God in their respective religions. Methodology: This paper is qualitative in nature and employs content analysis. Both al-Ghazali and Maimonides’ arguments are then analysed comparatively. Comparative theology is done to examine theological discourse as part of inter-religious dialogue. Main Findings: This study finds that their arguments differ in interpreting the necessary existent which Maimonides’ dual categorization of necessary existence distinguishes their arguments from there onwards. This entails the dual argument by which Maimonides affirmed God is the agent and cause of every occurrence. Meanwhile, al-Ghazālī only affirmed God is the agent through His will and concept of particularization. Applications: This paper is vital in discussing the concept of God through inter-theological dialogue. Novelty/Originality: Notwithstanding the significant number of texts on divine existence, the researcher found no study that specifically deals with al-Ghazālī and Maimonides’ discourses on the existence of God. Needless to say, comparisons of the concept of God in Islam and Judaism are very limited in contrast to Islam and Christianity. © Senin et al.